Sensory cues of a top‐predator indirectly control a reef fish mesopredator. Issue 2 (12th May 2015) - del Mar Palacios, Maria; Warren, Donald T.; McCormick, Mark I.
Abstract : Behavioural trophic cascades highlight the importance of indirect/risk effects in the maintenance of healthy trophic‐level links in complex ecosystems. However, there is limited understanding on how the loss of indirect top–down control can cascade through the food‐web to modify lower level predator–prey interactions. Using a reef fish food‐web, our study examines behavioural interactions among predators to assess how fear elicited by top‐predator cues (visual and chemical stimuli) can alter mesopredator behaviour and modify their interaction with resource prey. Under experimental conditions, the presence of any cue (visual, chemical, or both) from the top‐predator (coral trout Plectropomus leopardus ) strongly restricted the distance swum, area explored and foraging activity of the mesopredator (dottyback Pseudochromis fuscus ), while indirectly triggering a behavioural release of the resource prey (recruits of the damselfish Pomacentru s chrysurus ). Interestingly, the presence of a large non‐predator species (thicklip wrasse Hemigymnus melapterus ) also mediated the impact of the mesopredator on prey, as it provoked mesopredators to engage in an 'inspection' behaviour, while significantly reducing their feeding activity. Our study describes for the first time a three‐level behavioural cascade of coral reef fish and stresses the importance of indirect interactions in marine food‐webs.